A new species of Zasmidium associated with sooty blotch and flyspeck - Zhao, Wanyu; Hou, Yanmin; Bai, Jingke; Zhang, Wei; Gao, Liu; Zhang, Rong; Gleason, Mark L.; Sun, Guangyu (Phytotaxa, 2016)
During a survey to characterize the diversity of sooty blotch and flyspeck fungi in China, we obtained an isolate from a fungal colony exhibiting sooty blotch and flyspeck signs on the petiole of brown bollygum (Litsea glutinosa) in Guangxi, China. Based on phylogenetic analysis and morphological characterization, a new species, Zasmidium litseae is introduced. The new species is characterized by its swollen, straight or geniculate conidiogenous cells.